Peranan Partisipasi Masyarakat terhadap Pembangunan Desa Studi Pada Pembangunan Irigasi di Desa Namo Bintang Kecamatan Pancur Batu - Ompusunggu, Vina Maria (Universitas Medan Area, 2017)
This research has aims to describe and analyze society development participation in Namo Bintang Village, Pancur Batu District and to know how development in Namo Bintang Village to empower communities. This research belongs to qualitative research aiming to describe in detail and deeply about society participation in rural development. The instruments for collecting data are observation sheet and interview as the qualitative data and using the document. The village of Namo Bintang has an area of 495.2 hectares, The area of Namo Bintang is in the form of swamps and fields and abandoned cultivation. The livelihoods of the villagers of Namo Bintang are diverse. From the data of Namo Bintang Village, the majority of Namo Bintang's population work as farmers. The results showed that planning development process has not implemented well in Namo Bintang Village, Society participation in development planning in Namo Bintang Village was still low, the communities aren`t involved to conduct the priority of the activities which is able to their need. Therefore, it needs an accomplishment in participative development. The government should consider the suitability of the budgetary budget with Rural needs. The budgetary budget for the implementation of rural development should be given as a whole without having to be gradual so that the Implementing Team and the workers do not stop before the activity is completed, other than that need optimal socialization in the provision of information to the community in Namo Bintang Village so that they are more involved in the process, more so that the development planning can become the needs of the community. Keywords: Society Participation, Rural Development